Toxicological and analytical assessment of e-cigarette refill components on airway epithelia. (1st December 2016) - Singh, Jasjot; Luquet, Emilie; Smith, David; Potgieter, Herman; Ragazzon, Patricia
There are over 2.6 million users of e-cigarettes in the United Kingdom alone as they have been promoted as a safer alternative to traditional cigarettes. The addition of flavours and aromas has also proven to be popular with younger generations. In this review, we survey the range of studies in the short timeframe since e-cigarettes reached the market to draw attention to the health associated risks and benefits of their introduction. We complement this review with a case study reporting on the composition of selected e-cigarette refills with particular emphasis on the toxicological activity of its components on lung cells.